The opportunities and limitations of first nations forestry agreements in British Columbia: Collective experience of the Tl'azt'en nation & the future need for community-based resource management & decision-making. - Pun, Som Bahadur (Author); Halseth, Greg (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2015)
Since industrial clear-cut logging practice was introduced, First Nations people in British Columbia were mostly excluded from participation in the forestry sector and resource-based economic opportunities. In response to several Court ruling, the provincial government introduced the Forestry Revitalization Act in 2003 and has negotiated several forestry agreements with First Nations communities. As of April 2012, 172 First Nations communities across British Columbia, including the Tl'azt'en Nation have participated in certain aspects of these initiatives. However, to what extent First Nations communities such as the Tl'azt'en Nation have been able to meaningfully participate in the forestry sector through this new government initiative needs to be explored. This research study was conducted within the traditional territory of the Tl'azt'en Nation over the periods of 2011 and 2013. The qualitative semi-structured interviews were conducted between July 26 and August 10, 2012 involving both the Tl'azt'en and non-Tl'azt'en community members. The community consent and research agreement documents were obtained from the Tl'azt'en Nation prior to conducting the research study. This research study examines whether nor not the Tl'azt'en Nation was able to achieve their intended socio-economic goals through the recent forestry agreements, particularly since the signing of the short-term Interim Forest and Range Opportunities Agreement in 2008. My research demonstrates that while the community was able to obtain limited economic benefits from the recent forestry negotiations such as the Forest and Range Opportunities Agreement, the overall intended socio-economic objectives of the community were never fully realized due to a combination of several factors. By focusing on the unique needs and circumstances of the Tl'azt'en Nation, this thesis highlights the need for future community-based resource management and decision-making The original print copy of this thesis may be available here: ...